1990
DOI: 10.1083/jcb.111.5.2077
|View full text |Cite
|
Sign up to set email alerts
|

Differential phosphorylation of the gap junction protein connexin43 in junctional communication-competent and -deficient cell lines.

Abstract: Abstract. Connexin43 is a member of the highly homologous connexin family of gap junction proteins. We have studied how connexin monomers are assembled into functional gap junction plaques by examining the biosynthesis of connexin43 in cell types that differ greatly in their ability to form functional gap junctions. Using a combination of metabolic radiolabeling and immunoprecipitation, we have shown that connexin43 is synthesized in gap junctional communication-competent cells as a 42-kD protein that is effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
428
1
13

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 654 publications
(481 citation statements)
references
References 62 publications
39
428
1
13
Order By: Relevance
“…26,27 Hepa1-6 cells express Cx43, but, in general, at low levels as reported by Wilgembus et al 25 and confirmed by the present study. Immunoblot assay was carried out to examine if the HSVtk could induce some posttranslational changes of Cx43 protein.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…26,27 Hepa1-6 cells express Cx43, but, in general, at low levels as reported by Wilgembus et al 25 and confirmed by the present study. Immunoblot assay was carried out to examine if the HSVtk could induce some posttranslational changes of Cx43 protein.…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in gap junctional communication has been suggested as a common characteristic of cancer cells. 40,41 However, it was demonstrated that some transformed cells such as the mouse cell lines S180 and L929 express high gap junctional intercellular communication (GJIC), 26 indicating that the loss of GJIC is not necessarily associated with neoplastic transformation. However, even if the GJIC is present in these cells, they remain without functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cx43 electrophoreses as multiple isoforms when analyzed by SDS-PAGE, including a faster migrating form that includes non-phosphorylated (P0 or NP) Cx43, and at least two slower migrating forms, commonly termed P1 and P2 (Crow et al, 1990;Musil et al, 1990). Pulse chase analysis indicated that the Cx43 isoforms progress from P0 to P1 to P2 and the P2 isoform is associated with gap junctional structures (Musil & Goodenough, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The 46 -kDa band corresponded to the serine -diphosphorylated form, which is known to be the most active species of the functional connexon. 43 To check if the Cx43 expressed in the transduced cells adopted the proper surface topology, immunolocalization studies were performed ( Fig 5 ) using wild -type 9L cells and MDA -MB -435 cells as positive and negative controls, respectively (Fig 5A and B ). Spots of Cx43 were observed at the periphery of the breast -transduced cells ( Fig 5C and D ) .…”
Section: Introduction Of Cx43 In Mda -Mb -435 Cellsmentioning
confidence: 99%